El 'Segundo Signo' En El Cuarto Evangelio - Granados Rojas, Juan Manuel (Biblica, 2017)
This paper proposes a narrative reading of the 'second sign' in the Fourth Gospel. The plot of John 4,46-54 includes both a περιπέτεια and an ἀναγνώρισις, i.e. not only a healing, but also an acknowledgment. This narrative pattern delays solving the plot to stress a new comprehension of the faith in Jesus. Our analysis also suggests an all-inclusive explanation of several discrepancies between the Synoptic account and the Johannine one: the mention of βασιλικός rather than ἑκατόνταρχος, the doubling of ἐπίστευσεν (vv. 50.53), and the incongruity between the Royal Officer’s request and Jesus’ response (vv. 47.48).